Urgensi Pengaturan Fotografer Jalanan Sebagai Upaya Perlindungan Hak Privasi di Ruang Publik - Bernadine, Sheva Gelombang; Ruslie, Ahmad Sholikhin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Street photography is a form of artistic expression that captures social life spontaneously in public spaces. Behind its aesthetic and documentary value, this practice raises complex legal issues, particularly when it intersects with the boundary between the photographer’s freedom of expression and the individual privacy rights of the photographed subject. In the current legal framework, there are no specific regulations that clearly define the boundaries and legal responsibilities in the practice of street photography. Both photographers and the subjects they capture are placed in vulnerable positions: photographers risk criminalization on the grounds of privacy violations or defamation, while subjects who feel harmed lack a clear legal pathway to seek protection of their rights. This study examines the practice of street photography in Indonesia through a normative approach by analyzing the Criminal Code (KUHP), the Electronic Information and Transactions Law (UU ITE), and Law No. 27 of 2022 on Personal Data Protection (PDP Law), as well as connecting them to the principles of human rights as enshrined in the 1945 Constitution, the Universal Declaration of Human Rights (UDHR), and the International Covenant on Civil and Political Rights (ICCPR). The findings emphasize the need for the establishment of more specific regulations to create a balance between the rights of photographers and the rights of photographic subjects, thereby achieving legal certainty, justice, and the protection of human rights in the digital era.